VASCULAR AGE AND TARGET ORGAN DAMAGE IN THE MIDDLE-AGED UNTREATED PATIENTS WITH UNCOMPLICATED ESSENTIAL ARTERIAL HYPERTENSION. (June 2018) - Ostroumova, O.; Kochetkov, A.; Ostroumova, T.; Parfyonov, V.; Borisova, E.; Perepelov, V.
Abstract : Objective: to evaluate relationships between vascular age (VA) and target organ damage (TOD) in the middle-aged naive patients with grade 1–2 essential arterial hypertension (EAH). Design and method: Case-control study. We examined 60 naive patients with uncomplicated grade 1–2 EAH (mean age 53, 6 ± 0, 8 years). Transthoracic echocardiography (Vivid 7 Dimension system, GE) with calculation of myocardial stiffness parameters was performed in all patients. 2-D speckle tracking echocardiography data were acquired for determination of LV myocardial global longitudinal peak strain (LV GLPS). Cardio-ankle vascular index, ankle-brachial index and augmentation index (AI) were measured using VaSera-1500N system. Brain damage was evaluated by magnetic resonance imaging (MRI) using MAGNETOM Skyra 3.0T, Siemens AG. Arterial spin labeling MRI sequence was applied to analyze cerebral blood flow (CBF). All the patients underwent the neuropsychological assessment with Montreal Cognitive Assessment (MoCA), Trail Making test (part A and part B), Stroop Color and Word Test, verbal fluency test, 10-item word list learning task. VA was calculated by Framingham Heart Study risk tables and SCORE project scales. Results: VA calculated by Framingham Heart Study risk tables (70, 6 ± 1, 4 years) as well as VA estimated by SCORE project scales (59, 1 ± 1, 5 years) was significantly higher than chronological one (p < 0, 001 and p < 0, 01, respectively). VA demonstrated stronger associations with LV GLPS and tissue Doppler-derived left atrial strain (r = 0, 271; p < 0, 01 and r = −0, 206; p < 0, 05 for the VA by SCORE; r = 0, 401; p < 0, 001 and r = −0, 210; p < 0, 05 for the VA by Framingham Heart Study). Only AI closer correlated with VA: r = 0, 447 for the VA by SCORE and r = 0, 449 for the VA by Framingham Heart Study; p < 0, 001 in both cases. VA by Framingham Heart Study negatively significantly correlated with MoCA score (r = −0, 282; p < 0, 05), verbal fluency test score (r = −0, 246; p < 0, 05), right sided CBF (r = −0, 374; p < 0, 01) and left sided CBF (r = −0, 392; p < 0, 01). Right- and left sided CBF also demonstrated significant associations with VA calculated by SCORE project scales (r = −0, 326; p < 0, 01 and r = −0, 298; p < 0, 05). Conclusions: VA, especially estimated by Framingham Heart Study risk tables, is associated with cardiac, vascular and cerebral TOD in the middle-aged naive patients with uncomplicated grade 1–2 EAH.